WORK LIFE INTEGRATION AND MENTAL HEALTH: QUANTITATIVE STUDY OF EMPLOYEE WELL BEING - Jagdale, Supriya Mahesh; Bhaskar, Mahesh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
With an emphasis on employee well-being, this study investigates the connection between work-life integration and mental health. Achieving a healthy balance between work and home life is essential for mental health and overall productivity given the complexity of current professional demands. This research used a quantitative methodology to evaluate important facets of work-life integration and its impact on stress levels, job satisfaction, and emotional well-being. The sample size consisted of 230 respondents with a range of professional backgrounds. Structured questionnaires were used to gather data, and statistical analysis showed a strong relationship between better mental health outcomes and successful work-life integration. The results emphasize how crucial it is for organizations to have policies that enable flexible work schedules and mental health support networks.